Differentiated Impacts of Enterprise Information Systems on Financial Performance: A Meta Analytic Comparison of ERP, CRM, BI, and DSS - Sugianto; Puspitasari2, Devi (Indonesian Scientific Publication, 2025)
Enterprise Information Systems (EIS) including ERP, CRM, BI/BA, and DSS play critical roles in enhancing firm performance. However, their financial impacts vary across contexts, system types, and implementation designs. This study aims to systematically compare the financial effects of these systems using subgroup meta analysis, providing clarity on their differential contributions. A total of 120 studies were analyzed, focusing on three core financial outcomes: return on assets (ROA), return on sales (ROS), and revenue growth. Studies were selected from major IS meta analyses and empirical sources. Effect sizes were standardized using Fisher’s z, Hedges’ g, and log ratio transformations. A random effects model was applied, and subgroup analyses were conducted based on IS type and moderator variables including industry, region, firm size, and study design. CRM systems yielded the highest effect sizes (Cohen’s d = 0.67–0.75), especially in service sectors and developed markets. ERP systems showed moderate but consistent impact (d ≈ 0.54) through operational efficiency, while BI/BA (d ≈ 0.60) facilitated strategic planning. DSS contributed modestly (d ≈ 0.50). Moderator analysis revealed that larger firms and developed economies benefit more significantly from IS investments. Publication bias tests indicated some overestimation in cross sectional studies. These findings support the Resource Based View and complementary assets theory: IS value depends on integration with organizational capabilities. EIS types yield distinct financial benefits. CRM is optimal for rapid revenue and retention gains; ERP for internal efficiency; and BI for long term insights. Strategic alignment and contextual readiness determine ROI. The study offers theoretical and practical guidance for evidence based IS investment.